The process of development to happiness on Buddhism - ศิริรัตน์ นิรันดร์ (Journal of Buddhist Studies Chulalongkorn University, 2019)
This article discusses the process of developing well-being and happiness by practicing Dhamma, as humans’ greatest desire is to achieve happiness or to overcome suffering. In Buddhism, it is said that practicing Dhamma is a way out of suffering as it is a way for human beings to develop their full potential, which will lead to a cessation of suffering on every level, thus enabling them to achieve happiness. Practicing Dhamma in Buddhism includes right and systematic physical, verbal, and mental actions. Once followed, humans will reap the benefits of such practice. That is, they will be freed from cravings and sorrows, they will be able to continue to develop their intelligence, and will finally attain the final fruit – nirvana – which will be the cessation of all sufferings.